EFFECT OF β-LACTAM ANTIBIOTIC ADDITION ON IN VITRO AXILLARY SHOOT GROWTH OF POTATO (Solanum tuberosum L.) - Hidayat (Nim : 11414042), Rahmat
Pathogen-free of potato seed was highly needed. The propagation of potato using plant tissue culture technique with antibiotic application widely used to produce pathogen-free plant. Antibiotic was also used as selective agent on plant genetic transformation. On the other hand, it has retarded plant growth. The study was conducted to evaluate β-lactam antibiotic (amoxicillin and cefotaxime) effect on in vitro axillary shoot growth of potato. Antibiotic applied through explant soaking in antibiotic solution and antibiotic addition to culture medium. Then, explant was cultivated on MS + BAP 0.02 ppm. After that, it was subcultured on same medium 2 times every 3 weeks without explant soaking in antibiotic treatment. The research was carried out by completely randomized design with 3 factors: antibiotic: amoxicillin and cefotaxime; antibiotic concentrations: 0, 125, 250, 500 ppm; and duration of explant soaking in antibiotic solution: 30 and 60 mins. Plant growth parameters: number of nodes produce shoot, number of nodes/shoot, and shoot length was evaluated every 3 weeks, while shoot multiplication rate was counted every subculture. Data gained statistically analyzed using ANOVA (Analysis of Variance). The result showed that number of nodes produce shoot was not affected by antibiotic concentration in the medium, but it was affected by explant soaking in antibiotic solution treatment. Number nodes produce shoot was Ã‚Â± 1,5 nodes at post-treatment stage and only 1 node at 1st and 2nd shoot subculture stage. Medium with antibiotic addition gained the higher result than control on number of nodes/shoot, shoot length, and shoot multiplication rate parameters. The highest nodes/shoot showed on cefotaxime 125 ppm treatment at 2nd shoot subculture stage, it was 10,69 Ã‚Â± 2,83 nodes/shoot. Shoot length parameter has the highest result on cefotaxime 125 ppm treatment at 2nd shoot subculture stage, it was 7,64 Ã‚Â± 1,5 cm. The fastest shoot multiplication rate showed on cefotaxime 250 ppm treatment, it was 2,44 Ã‚Â± 0,75 shoots/3 weeks at 1st - 2nd shoot subculture stage.